IbM KRIPIK TEMPE - Eris Tri Kurniawati (Studi Kasus Inovasi Ekonomi, 2016)
ZTempeh chip is one of the specialties that are veryattached to each person who visited Malang city. As oneof the culinary icon, chips tempeh has a promisingmarket developed to provide an adequate income forMalang city residents, especially for home industry.Sanan is a sub-districts where there are many small -scale tempeh chip producer, and because there are manyother similar businesses tempeh chips sited in the samelocation then known as the center tempeh chips inMalang. On the basis of these considerations we try toprovide guidance and assistance to owner of tempehchips home industry in order to develop a sustainableand consistent growth in future time. In theimplementation we chose “Agista” tempeh chipsproducer as partner in this community service activities.Its business has been running since 2008 with tempehchips as a core product which divided into severalflavors besides that, it also has another chip products butnot too dominant in marketing. Things that we want todevelop from this tempeh chip producer is provideassistance in the management of financial records ,thedevelopment of managerial and also help them toprovide additional loan capital to develop the business ,which has been running.